Motivated Implicit Theories of Personality: My Weaknesses Will Go Away, but My Strengths Are Here to Stay. (April 2016) - Steimer, Andreas; Mata, André
Across six studies, this research found consistent evidence for motivated implicit theories about personality malleability: People perceive their weaknesses as more malleable than their strengths. Moreover, motivation also influences how people see themselves in the future, such that they expect their present strengths to remain constant, but they expect their present weaknesses to improve in the future. Several additional findings suggest the motivational nature of these effects: The difference in perceived malleability for strengths versus weaknesses was only observed for the self, not for other people. When the desirability of possessing a certain trait was manipulated, that trait was perceived to be more malleable when it was depicted as undesirable. And these different beliefs that people have about how malleable their traits are, and how they will develop in the future, were associated with their desire for change, which is higher for weaknesses versus strengths.